Antiviral and immunomodulatory effects of oral bovine lactoferrin therapy among patients with chronic hepatitis C. Issue 4 (October 2016) - El-Ansary, Mahmoud R.M.; Asaad, Ayman; Khalifa, Reham; Abdel Rahman, Amany T.; Abd Elsalam, Abd E.
Abstract : Introduction: Chronic hepatitis C (CHC) virus infection causes progressive liver disease. Bovine lactoferin (BLF) has several biological activities including modulation of immunoreactions and prevention of hepatitis C virus infection in cultured hepatocytes. The main objective of this study was to evaluate the antiviral activity and immunomodulatory effects of oral BLF therapy in comparison with pegylated interferon-α and ribavirin. This study included 60 patients with CHC. They were divided into two groups: Group I included 30 cases who received oral BLF tablets twice daily, and group II included 30 cases who were treated with combined therapy of pegylated interferon-α and ribavirin. Quantification of hepatitis C virus was carried out in both groups before starting therapy as well as 1 month and 3 months after therapy. After 1 month of treatment, there was a reduction in the level of viremia but without complete eradication of viremia in group I, whereas there was complete eradication of viremia in 10% of cases in group II. After 3 months of treatment, there was a marked reduction in the level of viremia, but there was no complete eradication in group I, whereas group II showed complete eradication of viremia in 40% of cases. Assessment of activated T cells and activated natural killer cells by measuring CD137 expression on CD4 +, CD8 +, and CD 56 + cells was carried out. The results of this study showed increased expression of CD137 among group I, whereas in group II CD137 expression decreased. In addition, the level of 2′-5′-oligoadenylate synthetase-1 was significantly elevated in cases of group I compared with group II after 1 month and especially after 3 months from the beginning of treatment. Conclusion: Oral BLF is a promising immunomodulatory drug; it is safe and has no side effects and can be used in combination with other antiviral drugs for the treatment of patients with CHC.